Touring as a Peircean habit - Knudsen, Daniel C.; Rickly, J.M. (Elsevier Masson, 2016)
The Peircean sign contains three parts: object, representamen (image) and interpretant (interpretation). •Interpretation in the Peircean system draws heavily upon the accumulated knowledge that an individual has built up over time. •Interpretation might be thoughtful, but more often it is an embodied habit. •The Peircean notion of habit inherently relates to the performative and is sufficiently general to incorporate emotionality.